Comparison of astigmatic correction with and without limbal marking during small-incision lenticule extraction. Issue 8 (August 2022) - Wang, Boyuan; Wang, Yan; Zhang, Jiamei
Abstract : Limbal marking-based manual compensation prior to SMILE can significantly reduce undercorrection and the error of axis in cases of moderate to high astigmatism. Abstract : Purpose: To compare clinical outcomes after correction of moderate to high astigmatism through small-incision lenticule extraction (SMILE) with and without limbal marking. Setting: Tianjin Eye Hospital, Tianjin, China. Design: Prospective randomized comparative case series. Methods: This prospective randomized control study included 240 unilateral eyes of 240 patients who underwent SMILE with astigmatism of more than 0.75 diopters (D). The eyes were randomly assigned to a marked group (120 eyes) or an unmarked control group (120 eyes). Manifest refraction was observed at the 3-month follow-up timepoint and evaluated using a vector analysis. Results: Postoperative astigmatism differed statistically significantly in the marked group (−0.08 ± 0.15 D) and the control group (−0.16 ± 0.24 D) at 3 months ( P = .001), and correction index, index of success, angle of error (absolute value), and magnitude of error were also significantly better in the marked group ( P < .05). There was a significant positive correlation between index of success and angle of error (absolute value) ( P < .001). Conclusions: Limbal marking–based manual compensation prior to SMILE was associated with a statistically significant reduction in undercorrection and error of axis in cases of moderate to high astigmatism, although the magnitude of the difference was small.